Renocardiac syndrome in a child with non-inherited connective tissue disease - N.S. Cherkasov; O.V. Davydova; L.I. Derbeneva; Yu.A. Lutsenko (LCC «Medicine-Inform», 2021)
N.S. Cherkasov, O.V. Davydova, L.I. Derbeneva, Yu.A. Lutsenko Astrakhan State Medical University, Astrakhan, Russian Federation This paper describes a case report of renocardiac syndrome in a child with non-inherited connective tissue disease (CTD). The importance of CTD is accounted for by its high occurrence (up to 80%) and controversial interpretation of phenotypic and visceral signs. In children, combined diseases more commonly develop under the effects of similar pathogenic factors or one disease impacts the development of another one. It was demonstrated that five organ systems are affected in 20% of children with CTD and three organ systems are affected in 40% of children with CTD. The most common conditions are cardiovascular and osteoarticular disorders followed by gastrointestinal disorders. Musculoskeletal and urinary tract disorders occurred in 33% and 19.5%, respectively. Renocardiac syndrome is of particular interest from the viewpoint of comorbidity. This case report addresses renocardiac syndrome in a 6-year-old boy. Eight phenotypic and six visceral signs of CTD were identified  in this child. Cardiac and renal abnormalities prevailed among internal signs. Therefore, CTD plays an important role in the development of renocardiac syndrome. Keywords: connective tissue disease, renocardiac syndrome, children, heart, kidney, comorbidity. For citation: Cherkasov N.S., Davydova O.V., Derbeneva L.I., Lutsenko Yu.A. Renocardiac syndrome in a child with non-inherited  connective tissue disease. Russian Journal of Woman and Child Health. 2021;4(2):184-188. DOI: 10.32364/2618-8430-2021-4-2-184-188.